Hypertension, type 2 diabetes, obesity, and p53 mutations negatively correlate with metastatic colorectal cancer patients’ survival - Ottaiano, Alessandro; Santorsola, Mariachiara; Circelli, Luisa; Perri, Francesco; Cascella, Marco; Sabbatino, Francesco; Capuozzo, Maurizio; Granata, Vincenza; Zappavigna, Silvia; Lombardi, Angela; Scrima, Marianna; Petrillo, Nadia; et al. (Frontiers in Medicine, 2023)
Introduction. We studied the predictive and prognostic influences of hypertension (HT), type 2 diabetes (T2D), weight and p53 mutations in metastatic colorectal cancer (CRC) patients. Patients and methods. T2D was diagnosed according to the ADA criteria. HT was classified according to the ACC/AHA guidelines. BMI (body-mass index) was calculated and classified according to the WHO criteria. TruSigt™Oncology 500 kit was applied to construct the genomic libraries for Next Generation Sequencing (NGS) analysis. The Illumina NovaSeq 6000 technological platform and the Illumina TruSight Oncology 500 bioinformatics pipeline were applied to analyze results. Overall survival (OS) was calculated through Kaplan-Meier curves. Univariate and multivariate analyses were performed to assess the relationships between clinical and/or molecular covariates. Associations between HT, T2D, BMI, p53 and clinical variables were evaluated by the χ2 test. P< 0.05 were considered statistically significant. Results. Two-hundred-forty-four patients were enrolled. One-hundred-twenty (49.2%), 110 (45.1%), and 50 (20.5%) patients were affected by overweight, HT, and T2D, respectively. DC (disease control) was achieved more frequently in patients without T2D (83.1%) compared to the diabetic ones (16.9%) (P=0.0246). DC, KRAS mutational status, T2D, BMI and concomitant presence of T2D, BMI, and HT associated with survival (P<0.05). At multivariate analysis, age (>65y vs <65y), response to first-line chemotherapy (DC vs no DC), and concomitant presence of T2D, BMI, and HT (HR: 4.56; 95% CI: 2.40-8.67; P=0.0217) emerged as independent prognostic variables. P53 was mutated in 31/53 analyzed cases (60.4%). The most frequent gene variants were p.Arg175His and p.Cys135Tyr. High BMI (>25 Kg/m2) associated with occurrence of p53 mutations (P<0.0001). P53 mutated patients presented a worse prognosis compared to the wild-type ones (HR: 3.21; 95% CI: 1.43-7.23; P=0.0047). Conclusions. Diabetic, hypertensive and overweight metastatic CRC patients are a negative prognostic subgroup deserving specific therapeutic strategies. P53 mutations associate with prognosis and BMI unrevealing complex and unexplored connections between metabolism and cancer occurrence.